Needle-like CoP/rGO growth on nickel foam as an efficient electrocatalyst for hydrogen evolution reaction. (26th February 2021) - Yang, Zhaoxia; He, Rui; Wu, Huimin; Ding, Yu; Mei, He
Abstract: In this work, CoP/NF is synthesized at different temperature (250 °C, 300 °C, 350 °C) (denoted as CoP/NF-T, T = 250, 300, 350). Then, CoP/NF-300 with the best performance towards hydrogen evolution reaction (HER), is used to synthesize compounds with different ratio of reduced graphene oxide (rGO) (CoP/rGO/NF-X, X (quality ratio of rGO/CoP) = 1, 3, 5). In terms of morphology, under the synergistic effect of rGO, uniform and dense CoP provides the possibility to increase the electrochemical area. While CoP/rGO/NF-3 shows the minimum overpotential of 136 mV to drive 50 mA/cm, and the smallest Tafel slope 135 mV/dec among as-synthesized materials. Furthermore, CoP/rGO/NF-3 has good stability during at least 25 h. These result can be construed as the large electrochemical active area, high conductivity and long-time stability. Graphical abstract: Synthesis and Electrocatalytic Activity of CoP/rGO/NF towards Hydrogen evolution reaction have been prepared successfully. And the CoP/rGO/NF with quality ratio of rGO/CoP = 3 (CoP/rGO/NF-3) has the best catalystic performance towards HER. Image 1 Highlights: CoP/rGO/NF composites were successfully synthesized by a two-step process. CoP/rGO/NF-3 exhibited better catalytic performance than other materials. CoP/rGO/NF-3 is expected to be a promising substitute for Pt.